Clinical trial and therapeutical progress of COVID-19 treated with remdesivir: A review - Anna Maria Manullang; Monia Agni Wiyatami; Mahulauw, Muhammad Azril Hardiman (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2021)
Coronavirus disease 2019 (COVID-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) that first reported in Wuhan City, China. Most confirmed cases of COVID-19 develop mild, moderate, severe to critical symptoms. One of the therapies given and of concern is remdesivir. Remdesivir is an antiviral with a broad spectrum that has activity against various types of viruses including Middle East respiratory syndrome coronavirus (MERS-CoV) and SARS-CoV. The aim of this review was to evaluate the clinical trial and the therapeutical progress of remdesivir in the treatment of COVID-19 patients. Databases used for this review were Google Scholar, JAMA, PubMed and Science Direct library. The inclusion criteria were covering any literature using remdesivir in clinical studies and COVID-19 therapy published from December 2019 to October 2020. Overall no pattern of laboratory abnormalities and clinically significant changes in vital signs or ECG shifts was observed in patients receiving remdesivir. The decision to use remdesivir in COVID-19 treatment should consider its potential benefits and risks.